Tutelas y curatelas en la época moderna: un estudio de casos en la Andalucía rural - Tovar Pulido, Raquel (Universidad de Málaga. Facultad de Filosofía y Letras, 2020)
guardianship and curatorship, family heritage, notarial protocol, minority of age, legal representative, century XVIII
Guardianship and curatorship in modern Times: a case study in rural Andalusia (18TH century)
Keywords: Mujeres - Situación social - Siglo XVIII; Tutela y curaduría; Herencia familia; Protocolo notarial; Minoría de edad; Representante legal; Siglo XVIII; Guardianship and curatorship; Family heritage; Notarial protocol; Legal representative; Minority of age; Century XVIII